2015
DOI: 10.21773/boun.29.2.3
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Self-Image Congruence Differences between Materialistic and Non-Materialistic Consumers

Abstract: This research aims to determine whether there are differences in the self-image congruence between materialistic and non-materialistic consumers towards different product categories (social and private consumption products). The study was carried out on the students of Erzurum Ataturk University using the survey method. Results indicate that there are significant differences in the self-image congruence between materialistic and non-materialistic consumers. Additionally, non-materialistic consumers choose prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
1
0
1
Order By: Relevance
“…In line with these results, some studies claim that through the food choice it is possible to express the self-concept [29,30] and to take care of personal health [31,32], becoming a possible key that drives and motivates consumers towards certain purchases rather than others. In support of this argument, previous studies also revealed that emotional and personal investment, beyond the motivation, is a fundamental aspect in orienting consumers' purchases [33][34][35].…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 76%
“…In line with these results, some studies claim that through the food choice it is possible to express the self-concept [29,30] and to take care of personal health [31,32], becoming a possible key that drives and motivates consumers towards certain purchases rather than others. In support of this argument, previous studies also revealed that emotional and personal investment, beyond the motivation, is a fundamental aspect in orienting consumers' purchases [33][34][35].…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 76%
“…Seperti yang diketahui secara luas, banyak konsumen menggunakan produk sebagai sarana untuk menunjukkan status mereka di masyarakat atau untuk mendapatkan status tertentu secara umum. Dengan cara ini, orang mendapat manfaat dari produk dan merek dengan mentransfer nilai-nilai mereka kepada diri mereka sendiri dan dengan memproyeksikan pesan tertentu kepada orang lain di sekitar mereka (Emre Başar & Ünal, 2016).…”
Section: Self-image Congruenceunclassified